Images as Preachers The Role of Marian Imagery in the Religious Indoctrination of the Moriscos of the Albayzin of Granada. - Sánchez, Amanda Valdés (Medieval Sermon Studies, 2023)
This paper explores how Hernando de Talavera (1428–1507), the first bishop of Granada, used the cast sculptures of the Virgin commissioned by Queen Isabella the Castile (1451–1504), for the parishes of the Albayzín, the Morisco quarter, as an essential tool for his missionary activity among Granada’s native Islamic population. It enquires how Talavera granted these Marian cast sculptures a central role in the Albayzin’s liturgical celebration, mediating their interpretation by devotional texts, such as his Marian liturgical works or his translation and commentary of the Vita Christi of the Franciscan Francesc Eiximenis (1327–1409), through which he wished to present these images as representations of an ‘Islamicate’ vision of Mary, as an enlightened prophetess who would function as the ideal preacher to instruct the newly converted Morisco population in the principles of their new faith.